FORENSIC RADIOLOGY IN DOMESTIC VIOLENCE INVESTIGATIONS: A MULTIPROFESSIONAL ROLE OF NURSING AND SPEECH THERAPY (REMUNOM, 2026)
OBJECTIVE: This study aims to identify the role of the multidisciplinary team, mainly speech therapists and nurses, with the help of forensic radiology, in providing support to victims of domestic violence and to analyze the challenges faced by available health services. INTEGRATIVE LITERATURE REVIEW: The literature highlights the essential nature of qualified and attentive listening by health professionals, ensuring confidentiality so that victims can recount their experiences and feel safe. The relevance of multidisciplinary care to fully meet the needs of these victims is also emphasized. However, several barriers are identified, such as the lack of coordination between services and professionals, inadequate physical infrastructure, difficulties in accessing support networks, the absence of clear protocols, and the occurrence of revictimization. The unpreparedness of health professionals, resulting from gaps in training and incipient qualifications, leads to inadequate approaches and biased practices, which further weakens women in situations of violence. FINAL CONSIDERATIONS: It is concluded that it is imperative that Basic Health Units develop health actions related to this theme, invest in the training of Primary Health Care professionals as well as the multidisciplinary team, and implement prevention strategies, offering effective support and assistance services to women in situations of violence.